Epistemology of Islamic and Western Perspectives (Teaching The Concepts of Scientific Thinking for Elementary-Age Children) - Ernawati, Tuti; Salminawati, Salminawati (Jurnal Basicedu, 2022)
Epistemology related to philosophy can be likened to a branching tree. The tree of philosophy has branches in the form of subdisciplines. Philosophy of science, ethics, aesthetics, philosophical anthropology and metaphysics. Epistemology as a branch of philosophy is devoted to the sources of knowledge. To arrive at an understanding of Islamic epistemology, it is necessary to use a genetivus subjectivus approach, which places Islam as the subject and object of epistemology. Epistemology as a result of human reason does not intend to interpret Islam, but aims at how to acquire knowledge, how the methodology of knowledge, the nature of knowledge and so on related to epistemology. So by itself Islamic epistemology studies Islam itself, or in other words epistemology according to Islam. This formulation makes a distinction between Islamic epistemology in general. Islamic epistemology in addition to general epistemology concerns relevance as a source of knowledge and inspiration. Epistemology generally assumes that truth is human-centered because humans have the authority to determine knowledge. This paper tries to compare epistemology in the Islamic and Western worlds as teaching the conception of thinking for elementary age children.